A search for OB stars in the field of the galactic OB association Bochum 7 : I. UBV-IR photometry and optical spectroscopy - Corti, Mariela Alejandra (2007)
Context. The presence of a Wolf-Rayet star, WR12, at α = 8 h44m47.2s, δ = -45°58′55. 5″ (J2000.0), triggered the search for a surrounding OB association now known as Bochum 7. Several papers have dealt with the existence of Bo 7, but none actually included spectral types of the stars. To assure the spectral types of members of the association, it is essential to have spectral images of them. Aims. In this paper we present previously unpublished spectra of OB stars over a 30 arcmin field covering the estimated field of the galactic OB association. Methods. From UBV aperture photometry, OB star candidates were selected, and optical spectroscopic observations were obtained for these in CASLEO, Argentina. Results. 63 stars were classified as OB type, including 8 stars already present in the LSS catalogue, and 37 of these 63 stars did not have a well-known spectral type. The OB stars were used to test the properties of the interstellar dust in the line of sight and the relation between the diffuse interestelar band at 4428 A, which grows linearly with E(B-V) until 1 mag. Combining our data with 2MASS IR photometry we tested and confirmed that derivation of stellar parameters from our photometry, using the CHORIZOS code, is highly reliable.